Preparing Child Welfare Practitioners: Implications for Title IV-E Education and Training Partnerships. Issue 3 (27th May 2018) - Griffiths, Austin; Royse, David; Piescher, Kristine; LaLiberte, Traci
ABSTRACT: High rates of child welfare practitioner turnover remain a national problem with significant consequences. Title IV-E education and training programs prepare child welfare practitioners for this line of work with the intent that they will create long term careers. This study analyzed qualitative data from a 2016 statewide electronic survey launched to obtain frontline child welfare practitioner feedback about workforce turnover and assist the agency in retention efforts. Practitioner insight resulted in 189 responses specifically related to improving the state's Title IV-E supported education and training program–the "Academy." A qualitative thematic analysis identified three main themes: making it more realistic and hands on (n = 104), needing additional training and specific content (n = 45), and feeling overwhelmed with the experience (n = 40). Practitioner feedback illustrated the existing tensions with using a blended model to educate and train the workforce. Implications for Title IV-E education and training partnerships are discussed.